Enhanced Charge Carrier Mobility in Two‐Dimensional High Dielectric Molybdenum Oxide. (23rd October 2012) - Balendhran, Sivacarendran; Deng, Junkai; Ou, Jian Zhen; Walia, Sumeet; Scott, James; Tang, Jianshi; Wang, Kang L.; Field, Matthew R.; Russo, Salvy; Zhuiykov, Serge; Strano, Michael S.; Medhekar, Nikhil; et al.
<x xml:space="preserve">Abstract</x> We demonstrate that the energy bandgap of layered, high‐dielectric α‐MoO3 can be reduced to values viable for the fabrication of 2D electronic devices. This is achieved through embedding Coulomb charges within the high dielectric media, advantageously limiting charge scattering. As a result, devices with α‐MoO3 of ∼11 nm thickness and carrier mobilities larger than 1100 cm2 V−1 s−1 are obtained. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>